2024
DOI: 10.1111/cns.14680
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric similarity differences in drug‐naive Parkinson's disease correlate with transcriptomic signatures

Yajie Wang,
Yiwen Xiao,
Yi Xing
et al.

Abstract: BackgroundDifferences in cortical morphology have been reported in individuals with Parkinson's disease (PD). However, the pathophysiological mechanism of transcriptomic vulnerability in local brain regions remains unclear.ObjectiveThis study aimed to characterize the morphometric changes of brain regions in early drug‐naive PD patients and uncover the brain‐wide gene expression correlates.MethodsThe morphometric similarity (MS) network analysis was used to quantify the interregional structural similarity from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“… 21 In addition, MSN may be perceived as a neuroimaging characteristic that connects alterations in brain structure to transcriptional information. 22 , 23 Recent studies have shown that clinical abnormalities of the MSN in diseases such as Parkinson's disease, 24 schizophrenia, 25 and major depressive disorder 22 are strongly correlated with the brain expression of disease‐related genes, revealing the transcriptome and cell pattern vulnerability of the regional brain to neurogenetic diseases. 23 Although the use of MSN is a reliable and powerful method, morphological differences in PSP have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“… 21 In addition, MSN may be perceived as a neuroimaging characteristic that connects alterations in brain structure to transcriptional information. 22 , 23 Recent studies have shown that clinical abnormalities of the MSN in diseases such as Parkinson's disease, 24 schizophrenia, 25 and major depressive disorder 22 are strongly correlated with the brain expression of disease‐related genes, revealing the transcriptome and cell pattern vulnerability of the regional brain to neurogenetic diseases. 23 Although the use of MSN is a reliable and powerful method, morphological differences in PSP have not been investigated.…”
Section: Introductionmentioning
confidence: 99%